Gambaran Penerapan Prinsip Benar Pemberian Obat di Rumah Sakit PKU Muhammadiyah Yogyakarta Unit II - Fatma Siti Fatimah (Alma Ata University Press, 2016)
Patient safety incidence make adverse patient and cause loss of life. Drug administration errors in Indonesia is the highest incidence. Incidents can occur due to human error one of health workers. This study aims to describe the characteristics of the respondent in the application of the principles of correct drug administration in PKU Muhammadiyah Yogyakarta Unit II Hospital. This research type is descriptive quantitative. Respondents were taken by purposive sampling, were 32 nurses who fulfill the inclusion criteria. The instrument uses an observation sheet. Characteristics of respondents by age at most <25 years of 56.2%, based on sex is 90.7% female, long work is <1 year 68,8%, education D3 84.4%. The percentage of correct application of the principle of drug administration most is in enough category is 69.4%. Characteristics of respondents by age at most <25 years, gender is female, long work is <1 year, namely education D3. Application of principles of correct drug administration is in fair category.